2004
DOI: 10.1111/j.0952-3383.2004.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

General Education Teachers in the United Arab Emirates and Their Acceptance of the Inclusion of Students with Disabilities

Abstract: In this article, Dr Emad M. Alghazo and Dr Eman El. Naggar Gaad, both assistant professors at the Department of Special Education in the United Arab Emirates University, report on their research into the attitudes of mainstream teachers towards the inclusion of students with disabilities. The research took place in the Emirate of Abu‐Dhabi, the capital of the United Arab Emirates, and set out to explore the extent to which general education teachers there accept the inclusion of students with disabilities in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
115
5
15

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(144 citation statements)
references
References 18 publications
9
115
5
15
Order By: Relevance
“…Regarding the issue of gender, the study showed that women were more supportive towards the inclusion of special educational needs students than men, result that is in accordance with previous studies [3,41,44,42,62].…”
Section: Teachers Attitudes Toward the Inclusion Of Special Educationsupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding the issue of gender, the study showed that women were more supportive towards the inclusion of special educational needs students than men, result that is in accordance with previous studies [3,41,44,42,62].…”
Section: Teachers Attitudes Toward the Inclusion Of Special Educationsupporting
confidence: 90%
“…Teaching these students demands a higher level of preparation and specialised planning for the implementation of special education goals [3].…”
Section: Teachers Attitudes Toward the Inclusion Of Special Educationmentioning
confidence: 99%
“…Some works conclude that secondary education teachers have less positive attitudes towards inclusion than their colleagues from kindergarten and elementary school (Avissar, Reiter, and Leyser 2003), while other studies did not find significant differences between teachers from different grade levels (Avramidis, Bayliss and Burden 2000; variable gender is taken into account. Some studies state that female teachers are more tolerant towards inclusion than male teachers (Alghazo and Naggar Gaad 2004;Hutzler, Zach, and Gafni 2005), but others (Batsiou et al 2008;Cardona 2011) found no association between gender and teacher perceptions of inclusion.…”
Section: Law Of Quality Of Educationmentioning
confidence: 99%
“…For example, Loreman and colleagues (2005) found that teachers were mixed in their attitudes towards students with diverse needs and abilities with the least positive response towards students with behaviour, and particularly physically aggressive behaviour problems. Moreover, Alghazo and Gaad (2004), and Englebrecht and colleagues (2003), concluded from their studies that teachers found students with an intellectual disability as being more difficult to support than students with other types of disabilities. Dupoux, Wolman and Estrada (2005) compared the attitudes of teachers toward inclusion of students with diverse needs and abilities in Haïti and the United States.…”
Section: Factors Influencing Teachers' and Trainee Teachers' Attitudementioning
confidence: 99%